1991
DOI: 10.1159/000125743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heterologous Growth Hormones on Hypothalamic and Pituitary Function in Transgenic Mice

Abstract: The expression of the mouse metallothionein-I (mMT) promoter/human growth hormone (hGH) fusion gene in transgenic mice leads to female sterility and major alterations in the function of the hypothalamic-adenohypophyseal system. These alterations include increases in median-eminence norepinephrine turnover and plasma LH levels, and a decrease in plasma prolactin levels in intact males, and an increase in median-eminence dopamine turnover combined with the suppression of plasma prolactin levels in ovariectomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…Although hypothalamic DA was unaffected by GH, the DOPAC/DA ratio was significantly decreased in the hypothalamus. This result is consistent with reduced DA turnover in the hypothalamus in GH transgenic mice (Steger et al 1991). In the medulla, GH affected DA turnover in the opposite direction.…”
Section: Discussionsupporting
confidence: 86%
“…Although hypothalamic DA was unaffected by GH, the DOPAC/DA ratio was significantly decreased in the hypothalamus. This result is consistent with reduced DA turnover in the hypothalamus in GH transgenic mice (Steger et al 1991). In the medulla, GH affected DA turnover in the opposite direction.…”
Section: Discussionsupporting
confidence: 86%
“…In this regard, Johnston et al (1993) demonstrated that DA regulates D2R gene expression in normal rat pituitary cells. In hGH transgenic mice, presumably due to its PRL-like action, hGH is binding to PRL receptors of the tuberoinfundibular dopaminergic neurons and stimulates their function, thus suppressing PRL release (Bartke et al 1988;Steger et al 1991). A similar situation occurs in association with hyperprolactinemia when PRL feedback regulates its own release, in part by influencing the function of tuberoinfundibular neurons (Moore 1987) and by increasing the synthesis and release of DA 238 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the induction of GH resistance by GHR gene knockout is correlated with a significant reduction in fertility (Chandrashekar & Bartke 1998, Bartke 1999. Exogenous GH, conversely, increases circulating LH levels in dairy cattle (Schemm et al 1990) and the in vitro release of LH and FSH from rodent pituitary glands (Steger et al 1991, Tang et al 1993. The administration of bovine GH to GH-deficient Ames mice also increases plasma LH concentrations (Chandrashekar & Bartke 1993).…”
Section: Somatotrophic-gonadotrophic Interactionsmentioning
confidence: 99%